Negotiations in planning and urban land consolidation - Per Kåre Sky (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2020)
Negotiations are important in urban densification processes. In particular, integrative negotiations seem to be relevant. The conflicts between neighbors and developers can be challenging to resolve. Land readjustment is used in several countries to merge properties or reshape properties in conjunction with densification projects. Conflicts can be handled and reduced by land readjustment. Should such a measure be relevant in Norway, it is recommended, among other things, that a majority of landowners within a land readjustment area must be in favor. There is a need for changes in both the Land Consolidation Act and the Planning and Building Act. Voluntary land readjustment should also be encouraged.
Keywords: C78; K11; O20; 330; Land Consolidation; Land Readjustment; Negotiation; Urban Development